What Does Kautsar Look Like? Topical Interpretation Of Mustafa Muslim's Surah Al-Quran - Akbar, Firdaus Maulana (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2024)
This study alludes to the lake of Kautsar as written in Surah al-Kausar verse 1. Because many Muslims read Surah Kautsar but do not know exactly about it. To explain this kautsar, the author will use the interpretation of a contemporary mufasir, Mustofa Muslim from Egypt, who explains that Muslims will meet the Prophet Muhammad SAW at the Kautsar lake. From here the question arises in the author's mind, how is Mustofa Muslim's interpretation of Surah Kautsar, what method does Mustofa use to interpret this letter, to answer these questions, researchers used Library Research. The purpose of this study is to highlight the opinion of Mustofa Muslim as a contemporary traveler who presents his interpretation in a different way. to complete this discussion the author uses the maudhui interpretation method used by the author Mustofa Muslim. The results obtained are a new way used by Mustofa Muslim to interpret this letter by prioritizing the history of tsiqoh companions such as Ibn Abbas RA over other companions, prioritizing Hadith narrated by Imam Bukhori and adding faidah lessons taken from the letter, and the method used to interpret this letter is with the interpretation method of maudhui method specifically for the letter.